ANALISIS KESULITAN KEMAMPUAN KONEKSI MATEMATIS DILIHAT DARI PERBEDAAN JURUSAN DI SMK - Linda Faudziah; Nurainah Nurainah; Siti Nuryatin; Risna Maryanasari; Wahyu Hidayat (Departement of Mathematics Education, 2019)
Research is a purpose to describe competence of student math connection on main discussion of spldv and sptldv. Research method is a qualitatif description by describing indicator of math connection competence is eaziest and most difficult to student gained. Subject of this research is farmation class student and nurse class in the healthy SMK Surya global at least fourty students. Instrument is used question test of math connection competence. Based on analysis data that is the student have indicator well of conection competence on student's competence to comprehend how the ideas on math connection another and serve as a basis each other to deliver one unity intact, the students do the difficulties indicator connection in knowing and utilize connections between idea on math in farmation dept and nurse. But nothing difference conection competence of mathematics significant between farmation dept and nurse